Contemporary Reoccupation of the Limean Region: An Academic Proposal for Scientific Intervention in Patrimonial Sites. The Case of the Pre-Hispanic City of Cajamarquilla - Flores Apaza, Daniel Delfín (2018)
This text is an approximation to an intervention proposal for archaeological sites in the city of Lima, applied to the site of Cajamarquilla, located in the current political jurisdiction of Lurigancho, east of Lima. The proposal seeks to integrate this archaeological complex to the contemporary metropolitan city through the study of its history and the territorial understanding of its settlement, as well as the urban logics that have been built around during the last decades, and that have formed a social fabric underlying the physical transformations of the site and its surroundings. The article consists of two moments: a first part deals with the academic and theoretical discussion that exists around the occupation and intervention of heritage sites, thus questioning the overly conservative way in which pre-Hispanic sites are treated, and finding in the reoccupation of the pre-existence a key to a more appropriate treatment, depending on the scale of the place and its impact on the city. The elaboration of the specific proposal, in the second part, is based on the theoretical results found: concepts of conservation of the memory, the value of the ruin, spatial reoccupation, cultural resignification and international criteria for the preservation of the built heritage, are combined holistic way, approaching the site from all its perspectives, in the material and immaterial aspects, for a coherent and integral result, that benefits all the actors involved.